Microbial derived biomaterials: fabrication, processing, and food application - İncili, Gökhan Kürşad; Razavi, Roghayieh; Hayaloğlu, Ali Adnan; Abedinia, Ahmadreza; Mirmoeini, Seyedeh Sahar; Moradi, Mehran (Elsevier, 2024)
Over the last few decades, the demand for the commercial production of biomaterials from low-cost, readily available, and abundant sources has gained significant interest. Microbial biomanufacturing is a novel approach in which certain wild-type or genetically engineered microbial strains are exploited for biomaterial production, given that microorganisms can be operated as factories to produce advanced biomaterials with widespread application in agriculture, food, and medicine. Certain microbial cells, particularly lactic acid bacteria, and also Escherichia coli, Saccharomyces cerevisiae, Corynebacterium spp., Bacillus spp., and Pseudomonas spp., serve as biomanufacturers for the synthesis of high-value intracellular and extracellular biomaterials. This chapter discusses the fabrication of major biomaterials derived from microbial sources including postbiotics, biopolymers (bioplastics), and microbial colorants. Exploration has been undertaken to assess the viability of utilizing these bioactive microbial molecules in sustainable microbial-assisted strategies for applications, such as food processing, packaging, and preservation. © 2025 Elsevier Inc. All rights are reserved including those for text and data mining AI training and similar technologies.
Keywords: Agronomy discipline; biological substances; food products; materials in biotechnology; materials synthesis